Academic Publication Uncertainty and Publishing Behavior: A Game-Theoretic Perspective - Jo\~ao Ricardo Faria; Rajeev K. Goel (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper incorporates publication uncertainty in a game between researchers and journal editors and examines its effects on quantity and quality of published research. A stylized differential Stackelberg game between journal editors and academic authors is considered, where authors seek to maximize satisfaction from publications, while journal editors try to enhance reputations of their journals. Publication probability depends on the number of academic journals. Results show that greater journal competition, generally leading to reduced publication uncertainty, would increase author payoffs by increasing citations and publications. However, it is not clear whether the quality of published research is enhanced. Thus, changes in competition in publishing markets have the potential to exacerbate the quantity-quantity trade offs in research markets.
Keywords: A11; A14; C79; L19; 330; publication uncertainty; journals; publications; citations; research quality; authors; editors